Paralleled two-pass hexagonal algorithm for motion estimation - Yunsong Wu; Megson, G. (Eighth International Conference on High Performance Computing in Asia Pacific Region : proceedings : 30 November - 3 December, Beijing, China, 2005)
This paper presents a paralleled two-pass hexagonal (TPA) algorithm constituted by linear hashtable motion estimation algorithm (LHMEA) and hexagonal search (HEXBS) for motion estimation. In the TPA, motion vectors (MV) are generated from the first-pass LHMEA and are used as predictors for second-pass HEXBS motion estimation, which only searches a small number of macroblocks (MBs). We introduced hashtable into video processing and completed parallel implementation. We propose and evaluate parallel implementations of the LHMEA of TPA on clusters of workstations for real time video compression. It discusses how parallel video coding on load balanced multiprocessor systems can help, especially on motion estimation. The effect of load balancing for improved performance is discussed. The performance of the algorithm is evaluated by using standard video sequences and the results are compared to current algorithms